A spiro-centered thermopolymerizable fluorinated macromonomer: synthesis and conversion to the high performance polymer. Issue 31 (28th March 2017) - Wang, Yuanqiang; Luo, Yijie; Jin, Kaikai; Sun, Jing; Fang, Qiang
Abstract : A new spiro-centered thermopolymerizable fluorinated macromonomer is reported here. Abstract : A new spiro-centered thermopolymerizable fluorinated macromonomer is reported here. This four-functional macromonomer is synthesized by a convergent strategy, and shows a low melting point (93 °C) and good solubility in the common organic solvents. When heated to a high temperature, the macromonomer converts into a cross-linked network (PD1 ), which exhibits a T g of near 316 °C and a 5% weigh loss at a temperature of 417 °C in N2 .PD1 also shows a low dielectric constant ( D k = 2.58 at 30 MHz) and high hydrophobicity (a water contact angle of θ = 98°), as well as low water uptake (about 0.45%, kept in boiling water for 72 h). These results suggest that the macromonomer has a potential application in the production of the high performance polymers, in particular, it is very suitable for encapsulation resins or the coatings utilized in the microelectronics industry.